The Description of a Good English Teachers’ Behavior in Teaching - Husein, Hasan (English Education Department, 2023)
This research aims to analyze English Teachers’ Behavior in teaching and learning process. This research used a qualitative method The subject of this research was three English teachers of SMPN 12 Wonoasari. The results of this research showed that the English teachers at SMPN 12 Wonosari have good personalities and are good model teachers, and all teachers at SMPN 12 Wonosari create a plan to implement learning and understand the peculiarities of the students. The English teacher at SMPN 12 Wonosari is in charge of the teaching materials that will be presented to students during the learning process because each teacher has created a plan for the implementation of learning that includes all of the materials and activities that will be implemented in each meeting.